Physiotherapy management on sprain medial collateral ligament in sports injury: a literature study - Sergio Johan Putra; Lucky Anggiat (Universitas Udayana dan Diaspora Taipei Medical University, 2023)
Background: The risk of sports activities is injuries. There are two types of injury classification often experienced by athletes: acute trauma and overuse. The part of the body in sports that are quite common injuries due to body contact is the knee. Medial collateral ligament (MCL) injuries were one of the most common knee injuries in sports. The role of physiotherapy in MCL injury conditions is to improve knee conditions in athletes, prevent re-current of injuries, help heal the athlete's condition after MCL injury with existing modalities and help restore the condition, which aims to make the athlete able to return to play in their sport. Methods: This study used library research which takes online and offline data sources to refer to books and scientific articles related to examination and physiotherapy intervention in the condition of MCL sprain injury. Results: Physiotherapists must carefully examine every symptom that appears by examining the basic function of motion, palpation, specific test with a valgus stress test, and functional evaluation in conditions of MCL sprain injury. Conclusions: In athletes, physiotherapy interventions must be graded, like reducing acute injury symptoms, exercising using tools, and reducing pain in the first phase; the second phase with increasing functional ability, flexibility, range of motion, and returning muscle strength; in the third phase, muscle strength must increase as before, returning agility, balance, and flexibility; furthermore, in the fourth phase, the athlete is prepared to return to sport with strength training, flexibility, agility, and sport-specific exercise.